2014
DOI: 10.3389/fendo.2014.00061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physiological Levels of the Green Tea Extract Epigallocatechin-3-Gallate on Breast Cancer Cells

Abstract: Physiological concentrations of the green tea extract epigallocatechin-3-gallate (EGCG) caused growth inhibition in estrogen receptor α (ERα)-positive MCF7 cells that was associated with down-regulation of the ERα and reduced insulin-like growth factor binding protein-2 abundance and increased protein abundance of the tumor suppressor genes p53/p21. In contrast to MCF7 cells that have wt p53, EGCG alone did not change cell proliferation or death significantly in another ERα-positive cell line T47D that possess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 50 publications
3
40
0
Order By: Relevance
“…Coffee beans are one of the richest dietary sources of the antioxidants caffeine and the plant phenolic compound caffeic acid, both of which may be mechanistically involved in the cancersuppressive properties of coffee. Various dietary and lifestyle factors are also known to influence the sensitivity to cancer treatment (10,16). In line with this, our group recently showed in a subset of the present study cohort, that moderate to high coffee consumption was associated with improved disease-free survival among ER þ tamoxifen-treated women (17).…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Coffee beans are one of the richest dietary sources of the antioxidants caffeine and the plant phenolic compound caffeic acid, both of which may be mechanistically involved in the cancersuppressive properties of coffee. Various dietary and lifestyle factors are also known to influence the sensitivity to cancer treatment (10,16). In line with this, our group recently showed in a subset of the present study cohort, that moderate to high coffee consumption was associated with improved disease-free survival among ER þ tamoxifen-treated women (17).…”
Section: Introductionsupporting
confidence: 86%
“…In recent years, mechanisms involved in mediating cancer chemopreventive effects of naturally derived plant polyphenols from green tea and coffee have been widely studied in several neoplasias, including breast and prostate cancer (10)(11)(12)(13). However, there have been few translational studies on anticancer effects of coffee in relation to ER status in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It also caused increased cell death of another breast cancer cell line, MDA MB-231 which is estrogen receptor negative. Further it has been shown to increase sensitivity to tamoxifen treatment [23]. Wang et al showed that EGCG potentiates the effect of curcumin in causing growth inhibition and inducing apoptosis of MCF 7 breast cancer cells.…”
Section: Epigallocatechin-3-gallatementioning
confidence: 99%
“…EGCG is the major component of catechins found in green tea and exists in four active forms: (1)-epigallocatechin-3-gallate (EGCG), (2)-epigallocatechin (EGC), (3)-epicatechin-3-gallate (ECG), and (4)-epicatechin (EC) (Zeng et al, 2014). Catechins, which are polyphenols, constitute nearly 30%-40% of the dry weight of green tea (Lecumberri et al, 2013;Zeng et al, 2014), which is one of the most popular beverages in the world, after water.…”
Section: Introductionmentioning
confidence: 99%
“…Catechins, which are polyphenols, constitute nearly 30%-40% of the dry weight of green tea (Lecumberri et al, 2013;Zeng et al, 2014), which is one of the most popular beverages in the world, after water. EGCG is an important compound, as it has antitumor activity.…”
Section: Introductionmentioning
confidence: 99%